Exploring intraoperative hemorrhage and early recurrence in pelvic malignant solitary fibrotic tumors: a case report and literature review - Li, Dong-Mei; Tang, Dan; Qie, Ming-Rong; Hou, Min-Min (Frontiers in Oncology, 2025)
IntroductionSolitary Fibrous Tumor (SFT) is a rare mesenchymal tumor characterized by CD34-positive dendritic stromal cells that can differentiate into fibroblasts or myofibroblasts. Although commonly found in the pleura, these tumors can also occur in other locations, including the retroperitoneum, where a subset may show malignant behavior, leading to local invasion and metastasis.Case presentationWe report the case of a 60-year-old woman with progressive abdominal distension (3 months) and dysuria (2 months). Imaging revealed a 7.6cm × 10.1cm × 10.7cm right pelvic mass compressing the ureter and bladder. Surgical resection of the firm, hypervascular uterine mass with infiltrative margins was achieved. Immunohistochemistry demonstrated diffuse positivity for CD34, STAT6, Bcl-2, CD99, SW-1 and ER, with focal TP53 expression and 10% Ki-67 index, confirming malignant solitary fibrous tumor. Early postoperative surveillance MRI at one month detected local recurrence with regional lymph node metastases. Given the tumor’s aggressive biology, high operative risk for re-intervention, and lack of effective systemic therapy options, a multidisciplinary team recommended transition to palliative care. The patient remains alive after following up 8 months.ConclusionNeoadjuvant radiotherapy may benefit high-risk SFT cases nearing the limits of resectability, but current evidence highlights the challenges in managing aggressive pelvic malignant SFTs and emphasizes the need for ongoing research into effective treatment options while also aiming to stimulate discussion among scholars and encourage the sharing of experiences from similar cases to provide valuable insights for future diagnosis and treatment of malignant SFTs.